2016
DOI: 10.1111/jpc.13311
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anger in fathers of unsettled infants: A community cohort study

Abstract: Fathers of unsettled infants reported greater anger towards their infant and increased depressive symptoms by 4 months infant age, with these symptoms persisting 2 months later. Evidence-based interventions are needed for these fathers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 30 publications
2
36
0
1
Order By: Relevance
“…Despite decades of research, we still do not understand the cause, or causes, of infant colic. Previous research has suggested that maternal anxiety and depression are associated with infant colic, as well as paternal depression . A previous study by our group demonstrated that mothers with migraine were more than twice as likely to have a baby with colic, and another study similarly found an association between maternal migraine and infant colic .…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Despite decades of research, we still do not understand the cause, or causes, of infant colic. Previous research has suggested that maternal anxiety and depression are associated with infant colic, as well as paternal depression . A previous study by our group demonstrated that mothers with migraine were more than twice as likely to have a baby with colic, and another study similarly found an association between maternal migraine and infant colic .…”
Section: Introductionsupporting
confidence: 55%
“…To be able to adjust for potential confounding, several comorbidities known to be associated both with infant colic and with migraine in adults were assessed by self‐report …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the proportion of women with infants admitted to REPS annually in Australia, the problems documented here might be being experienced by thousands of Australian men (Fisher et al, 2011). However, the data also have implications for the approximately 300,000 men who have babies each year (Bayer, Hiscock, Hampton, & Wake, 2007), particularly, if their infants are unsettled (Cook et al, 2016;Smart & Hiscock, 2007). If women consult health service providers for their own psychological needs or unsettled behaviours among their infants, then routine assessment of the father's health should be considered and family-focused psycho-educational interventions recommended.…”
Section: Implications For Health Service Providersmentioning
confidence: 84%
“…However, the psychological needs of men whose partners and infants are admitted to REPS are poorly understood. While fathers of unsettled young infants report significantly poorer mental health than fathers whose infants are not unsettled (Cook et al, 2016;Smart & Hiscock, 2007), it is not known to what extent poor mental health associated with UIB persists beyond the early postpartum period.…”
Section: Introductionmentioning
confidence: 99%